Pan-Atlantic distribution patterns and reproductive biology of the bigeye thresher, Alopias superciliosus - Fernandez-Carvalho, Joana (2020)
The bigeye thresher (Alopias supercilious) is occasionally caught as bycatch in pelagic longline fisheries targeting tunas and swordfish. Still, it is one of the least known and studied of all pelagic sharks, which hinders assessment of the status of its populations. As part of an ongoing cooperative program for fisheries and biological data collection, information collected by fishery observers and through scientific projects from several nations that undertake fishing activities in the Atlantic (Japan, Portugal, Spain, Taiwan, Uruguay and US) was compiled and analyzed. Datasets include information on location, size, sex and, in some cases, maturity stage. A total of 5590 bigeye thresher records collected between 1992 and 2013 were compiled, with sizes ranging from 70 to 305 cm fork length (FL). Considerable variability was observed in size, with tropical regions recording a smaller mean size compared to other regions. The distribution of juvenile and adult specimens also showed considerable variability, and the sex ratios varied between regions and size classes. Median sizes at maturity were estimated at 208.6 cm FL for females and 159.2 cm FL for males. Pregnant females were recorded in the tropical northeast and southwest Atlantic, with these regions possibly serving as nursery areas. The biological and distributional patterns presented in this study provide a better understanding of different aspects of this species in the Atlantic, which can help managers adopt more informed and efficient conservation measures.